Detecting network attacks Model based on a long short-term memory LSTM - Jasi, Teba Ali; Jawhar, Muna M. Taher (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Nowadays, network-connected devices such as mobile phones and IoT devices are increasing, the types and numbers of these devices are increasing, the impact of successful attacks is increasing and the fear is growing due to the security effects when using them. In addition, a broader attack surface is available to identify and respond to these network attacks, different systems are used to prevent and stop Some of these systems consist of two layers, the first layer which provides Security and Intrusion Prevention is the firewall, while the second layer is the network intrusion detection system or attack detection system, if only the first layer represented by the firewall is used we cannot prevent attack, that’s why attack detection or malware detection systems are used along with a firewall.